2019
DOI: 10.1186/s41938-019-0131-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the entomopathogenic fungus, Beauveria bassiana, combined with diatomaceous earth on the red flour beetle, Tribolium castaneum (Herbst) (Tenebrionidae: Coleoptera)

Abstract: An assay was designed to evaluate the efficacy of each entomopathogenic fungus, Beauveria bassiana, and diatomaceous (DE) and their combinations at concentrations of 1 × 10 6 and 1 × 10 8 conidia kg −1 of wheat and 200 and 400 ppm, respectively, on the red flour beetle, Tribolium castaneum (Herbst) (Tenebrionidae: Coleoptera), infesting wheat. Percent mortality of T. castaneum was recorded after 7, 14, and 21 days. Percent mycosis on dead cadavers was assessed after 21 days. Alive adults were removed from pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The efficacy of various DE formulations and the different fungal species have been evaluated against stored-product insects in several studies (Vassilakos et al 2006;Athanassiou et al 2008;Rizwan et al 2019). However, in the present study, the insecticidal effect of T. harzianum and DE combinations was investigated in the stored common bean for the first time.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The efficacy of various DE formulations and the different fungal species have been evaluated against stored-product insects in several studies (Vassilakos et al 2006;Athanassiou et al 2008;Rizwan et al 2019). However, in the present study, the insecticidal effect of T. harzianum and DE combinations was investigated in the stored common bean for the first time.…”
Section: Discussionmentioning
confidence: 98%
“…Similar results were obtained by Riasat et al (2011) when wheat grains infested with R. dominica were exposed to B. bassiana alone and mixed with DE at different concentrations and found that the emergence of the progeny after 60 days of treatment was also highly suppressed (20.00 adults), when the maximum dosage rate of the synergised treatments was applied. Rizwan et al (2019) showed that the maximum progeny production of T. castaneum (62.67 adults) was achieved in wheat grains treated with a low concentration of B. bassiana (1 × 10 6 conidia/kg) alone, while the minimum progeny production (2.67 adults) was recorded in wheat grains treated with a high concentration of B. bassiana (1 × 10 8 conidia/kg) and a DE (400 ppm) combination.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Currently, biopesticides are being used for insect pest management due to less hazardous impact on the environment, beneficial fauna, and ultimately human health 21 , 22 . Entomopathogenic fungi (EPFs) have been used for the management of insect pests ranging from stored grain pest management 23 , laboratory testing 22 , greenhouse assay 21 , and field trials 24 . However, studies regarding the impact of these biopesticides including EPFs on the biological control agents naturally present in the field are still a researchable topic.…”
Section: Introductionmentioning
confidence: 99%
“…However, the success of EPFs is also associated with non-virulence/compatibility to biocontrol agents like predators and parasitoids, which should be tested before recommending to the farmers. Beauvaria bassiana (Balsamo) Vuillemin (Ascomycota: Hypocreales) is being used successfully against various insect pests such as Cnaphalocrocis medinalis 21 , Nilaparvata lugens 22 , and Tribolium castaneum 23 , Helicoverpa armigera 27 , Plutella xylostella 28 , Cosmopolites sordidus 29 , aphid species 30 , and many stored grain insect pests 26 . Metarhizium anisopliae (Metschnikoff) Sorokin (Hypoc., Clavicipitaceae) is another fungus that naturally grows in soil worldwide 31 and plays a key role as an active biological control agent for different insect pests 32 .…”
Section: Introductionmentioning
confidence: 99%